2008
DOI: 10.1002/eji.200838289
|View full text |Cite
|
Sign up to set email alerts
|

Glucose deprivation inhibits multiple key gene expression events and effector functions in CD8+ T cells

Abstract: We recently reported that differentiation of CD8 1 T cells from the naïve to the effector state involves the upregulation of glucose-dependent metabolism. Glucose deprivation or inhibition of glycolysis by 2-deoxy-D-glucose (2-DG) selectively inhibited production of IFN-g but not of IL-2. To determine a more global role of glucose metabolism on effector T-cell function, we performed gene array analysis on CD8 1 effector T cells stimulated in the presence or absence of 2-DG. We observed that expression of only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
263
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(296 citation statements)
references
References 34 publications
15
263
1
1
Order By: Relevance
“…To maintain their housekeeping functions T cells produce ATP mainly through catabolic processes that breakdown amino acids, glucose and lipids via OXPHOS (37,38). Upon Ag-specific activation, however, T cells undergo an immediate glycolytic switch to meet the energy demands for proliferation and for optimal effector function (46,47,59). Amino acids and lipids are then used for the production of molecules required to respond to infectious agents, and the generation of ATP is progressively more dependent on aerobic glycolysis (60,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain their housekeeping functions T cells produce ATP mainly through catabolic processes that breakdown amino acids, glucose and lipids via OXPHOS (37,38). Upon Ag-specific activation, however, T cells undergo an immediate glycolytic switch to meet the energy demands for proliferation and for optimal effector function (46,47,59). Amino acids and lipids are then used for the production of molecules required to respond to infectious agents, and the generation of ATP is progressively more dependent on aerobic glycolysis (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data indicate that T cells can choose which metabolic process (aerobic glycolysis versus mitochondrial respiration) to use to produce the required energy, depending on the availability of nutrients. T cell activation through TLR requires mitochondrial respiration, but not glucose, to fuel IFN-g production Previous studies have found that effector CD8 + T cells rely on glucose metabolism for optimal production of IFN-g (45)(46)(47). In this study, we asked whether TLR-mediated IFN-g production also depends on glucose availability.…”
Section: Both Aerobic Glycolysis and Mitochondrial Respiration Generamentioning
confidence: 97%
“…+ T cells has been shown to be glucosedependent (31)(32)(33). The HbA1c values and fasting glucose concentrations were, however, in the normal range in most of the children with advanced b cell autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Only phosphorylase kinase, ␥-1 (PHKG1) had no documented evidence of immune involvement, with its known function being as a key glycogenolytic enzyme. However, the dependence of T-lymphocyte activity on glucose metabolism suggests a potential role in immune function for this gene (29). In the reverse analysis of genes that overlapped between both bad prognosis groups, that is, the recurrent EPN phenotype and TTP negative correlates, only two genes were identified: programmed cell death-6 (PDCD6) and opsin-3 (OPN3), which are known to have roles in TCR-induced apoptosis and photoreception, respectively.…”
Section: Overlapping Genes Between the Nonrecurrent Epn Phenotype Andmentioning
confidence: 99%